(untitled) (Experimental biology, 2015)
In article questions of innovative technologies of the training, succeeded raditional methods of training are considered. Innovative activity (technology) covers all parties of didactic process: organization forms, contents and technology of training, educational cognitive activity. The method a case-stadi as the interactive method of training applied on chair of molecular biology and genetics of KAZNMU is considered in detail; in particular on the system subject “Congenital Developmental Anomalies of the Cardiovascular” at the first year.